Pesona Masigi Ogena (Masjid Agung) Keraton Wolio Kesultanan Buton - Idham Idham (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2012)
The objective of this research is to know the Masigi Ogena’s (Grand Mosque) morphology of the Wolio palace, the Buton Sultanate. Applying the explanative and descriptive approach, this research describes the existing archeology data and explains their meaning. The research shows that unique design of Masigi Ogena is meaningful; it denotes spiritual and religious thought and practices